DEVELOPMENT OF MOTORCYCLE CHASE MAINTENANCE LEARNING MODULE FOR STUDENTS OF CLASS XI AUTOMOTIVE LIGHT VEHICLE ENGINEERING AT SMK PIRI SLEMAN - Dwi Nopriadi S1; Subagyo; Sigit Purnomo (Universitas Sarjanawiyata Tamansiswa Yogyakarta, 2025)
This study aims to (1) Know the characteristics of Occupational Health and Safety (OSH)learning videos in the subject of Automotive Basic Technology Class X Automotive atYogyakarta Industry Vocational High School, (2) Know the feasibility of OSH learningvideos on Automotive Basic Technology subjects Class X Automotive at Yogyakarta IndustryVocational High School, (3) Know the response students on the Occupational Health andSafety (K3) learning video in the subject of Automotive Basic Technology class X Automotiveat the Industrial Vocational School of Yogyakarta.This research is a research and development (R&D) with a 4D (Four-D) development modelconsisting of the Define, Design, Development, Disseminate stages. The development mediais in the form of learning videos. The subject of this research is class X automotive at SMKIndustry Yogyakarta. The object of this research is the K3 learning video. Media feasibilityassessment is carried out by media experts and material experts. The instrument used is aquestionnaire / questionnaire. Data analysis techniques using quantitative descriptiveanalysis. The results of the study show that: this research produces K3 learning videos, K3learning videos are used based on the results of the material expert validation with